ANALYSIS OF WATER INGRESS OF COMPOSITE SANDWICH STRUCTURE ON CABIN FLOOR OF AIRBUS A330 AIRCRAFT USING ANSYS - Hermawan, Agus; Fitri, Muhamad (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Abstract - The rapid advancement of aviation technology necessitates rigorous structural evaluations to ensure safety and efficiency. This study focuses on analyzing water ingress in sandwich composite structures used in the cabin floor of the Airbus A330, employing Non-Destructive Testing (NDT) and simulation methods. Using thermography, areas with water ingress were identified, with darker regions indicating trapped moisture within the composite layers. Two cases were analyzed: one with areas requiring repair and another within acceptable damage limits as per the Structure Repair Manual (SRM). The study simulated the effects of pressure and temperature using ANSYS. Results revealed minimal pressure differences, with values ranging between 0 and 0.80 atm. Temperature simulations showed a range of 21°C to 24°C, suggesting potential condensation that could lead to water ingress. Structural simulations evaluated the composite's deformation, elastic strain, and stress distribution. The maximum deformation was 5.1138 mm, with elastic strain peaking at 0.0033772 mm/mm and stress von Mises reaching 591.74 MPa, well within the material's safety threshold. This research highlights the importance of periodic inspections and advanced simulation techniques in maintaining composite structures. Recommendations include utilizing additional NDT methods, such as ultrasonic testing, to enhance detection accuracy and investigating actual cabin conditions to refine future analyses.